Cardiac remodeling in elite young Asian female soccer players - Kim, Narae; Park, Hyunkyung; Sohn, Il Suk; Yang, In-Ho (Frontiers in Cardiovascular Medicine, 2024)
IntroductionAn athlete's heart (AH) varies depending on race, sex, age, and the type and intensity of training. Given that soccer is a common sport, evaluation of cardiac function in soccer players is important; however, few studies have analyzed adolescent soccer players. Therefore, this study, aimed to identify early changes in AH in soccer players by evaluating the echocardiographic findings of adolescent Asian female soccer players for whom existing data are scarce.MethodsWe evaluated 20 Korean female under-20 national soccer team players and 42 age-matched healthy females. Participants provided physical examination data such as height, weight, blood pressure, and pulse, along with echocardiographic results. On echocardiography, parameters related to the morphology of the left atrium (LA) and left ventricle (LV) and those related to the systolic and diastolic function of the LV were measured.ResultsThe athlete group had a lower blood pressure and pulse rate than the control group. Echocardiography indicated that both the LA volume index and LV volume in the athlete group were large by approximately 1.5 times compared with those in the control group. The LV wall thickness and mass index were also significantly large in the athlete group. For LV diastolic function, parameters indicating early diastolic filling were substantially higher in the athlete group than in the control group.ConclusionsAdolescent female soccer players exhibited differences in cardiac morphology and an enhanced diastolic function. Therefore, this study suggests that AH begins in adolescence, with changes in both morphology and function.